The requested mining concessions of coal in the Cerro del Tablazo of Desamparados (1845-1921) - Mora, Guillermo (2020)
This paper describes and analyzes the requested mining concessions in the Cerro del Tablazo during the 19th and first half of the 20th century. Although the exploitation of coal was developed at a site near the Metropolitan Area of San José, today there are really few people who know the presence of mineral coal there and that such resource was exploited in the past. The porpuse of the work is to spread the geological knowledge, particularly the existence of mineral coal in the Cerro del Tablazo. In order to reconstruct the history of coal exploitation in the site, a literature review was required. Results indicate that there was mining activity in the studied area which consisted on the extraction of coal from the subsoil to commercialize it in San José.